Answer:
Option (D)
Explanation:
Standard equation of a quadratic function is,
ax² + bx + c
Comparing this function with the given quadratic function,
f(x) = 2x² - 4x - 3
a = 2, b = -4 and c = -3
By using quadratic formula to get the value of x,
x =
![(-b\pm √(b^2-4ac) )/(2a)](https://img.qammunity.org/2021/formulas/mathematics/high-school/wdx2xjkgubv4pcnn37s0b10csihcharcix.png)
=
![(-(-4)\pm √((-4)^2-4(2)(-3)) )/(2(2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/qf8tpvt8tc4wj5v6740zrb8fbww0v2d6m9.png)
=
![(4\pm√(16+24))/(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/7plsy79j3az19dyv9oq6bkf01zef3f4wi0.png)
=
![(-4\pm √(40))/(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/wj93f7pmwvfe5lkl74olc9avfs8x6gpznq.png)
=
![(-2\pm √(10))/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/8urwez17zh9tgripgcqrn5r9lhci6uzd0p.png)
Therefore, Susie made a mistake in step IV.
Option (D) is the answer.